Effect of Sauropus androgynus leaf extract, fish oil and vitamin E on performance, egg quality and composition in laying hens - Santoso, U.; Fenita, Y.; Sulistyowati, E. (Diponegoro University, 2017)
The objective of this study was to obtain enriched eggs with low cholesterol content. Forty-eight laying hens (strain Dekalb Warren) aged 72 weeks were distributed into six treatment groups as follows: 1) Laying hens fed diet without Sauropus androgynus leaf extracts (SALE), fish oil and vitamin E (P0) as the control; 2) Laying hens were fed diet with 27 g SALE/kg diet, but without fish oil (P1); 3) Laying hens were fed diet with 27 g SALE/kg diet, 1.5% fish oil (P2); 4) Laying hens were fed diet with 27 g SALE/kg diet, 1.5% fish oil and 60 mg vitamin E/kg diet (P3); 5) Laying hens were fed diet with 27 g SALE/kg diet, 3% fish oil (P4); 6) Laying hens were fed diet with 27 g SALE/kg 3% fish oil and 60 mg vitamin E/kg diet (P5). Experimental results showed that the treatments affected (P <0.05) egg production, thick eggshell, egg white height, yolk color, the odor of eggs after the split (P <0.05). It was shown that the treatments had no effect on the contents of protein, fat, β-carotene of eggs but affected the contents of cholesterol and vitamin E of eggs. In conclusion, the treatments improved egg quality and increased egg Vitamin E but reduced egg cholesterol.